1997
DOI: 10.1148/radiology.203.1.9122402
|View full text |Cite
|
Sign up to set email alerts
|

Radiographically occult scaphoid fractures: value of MR imaging in detection.

Abstract: MR imaging has a high sensitivity for detection of fractures of the scaphoid bone and wrist not evident on plain radiographs and may enable early diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(86 citation statements)
references
References 0 publications
2
75
0
9
Order By: Relevance
“…By using E-MRT, we found 18 more occult fractures in 47 patients. This is in agreement with other studies, which reported occult fractures of the carpal bones detection of in up to half of the patients, using whole-body MR scanners (Gaebler et al 1996, Breitenseher et al 1997, Hunter et al 1997.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…By using E-MRT, we found 18 more occult fractures in 47 patients. This is in agreement with other studies, which reported occult fractures of the carpal bones detection of in up to half of the patients, using whole-body MR scanners (Gaebler et al 1996, Breitenseher et al 1997, Hunter et al 1997.…”
Section: Discussionsupporting
confidence: 93%
“…Whole-body MRI of the wrist (Imaeda et al 1992) has been reported to be better than other modalities for diagnosing fractures of the carpal bones (Lepisto et al 1995, Gaebler et al 1996, Breitenseher et al 1997). …”
mentioning
confidence: 99%
“…First, we included only studies published as a full report in English. We identified three potentially eligible nonEnglish studies [8,31,33], two of which [8,31] involved potential overlap of patient population with an included study [7]. Second, we did not test for publication bias, which hampers most metaanalyses of diagnostic tests [45].…”
Section: Discussionmentioning
confidence: 99%
“…38,64,72,74,75,88,91,[95][96][97][98][99][100] Investigators reported a variety of criterion standards, including clinical evalua- Figure 12. Ultrasound forest plots.…”
Section: Mrimentioning
confidence: 99%